HOW TO IMPROVE THE STUDENT ACADEMIC PERFORMANCE - Rahayu, Sri; G.P.A. Hidayat, Wanda (International Journal of Psychosocial Rehabilitation, 2020)
The performance of a higher education institution was one of the important factors determining success in producing quality graduates. Academic achievement obtained by students was considered the success of a student and the learning system at the institution. The academic quality was also inseparable from the background of the student itself. Besides, the system and climate of teaching and learning created in the educational environment. The purpose of this study was to describe students’ academic performance and the factors that influence the improvement in the academic performance of undergraduate students in the Psychology department at Airlangga University. This research used a quantitative approach with a descriptive survey research design. Based on the results of research conducted, it concluded that student performance, the program study performance, and university performance affect student’s academic performance, both simultaneously and partially for undergraduate students at the Faculty of Psychology, Airlangga University.